Reduced Tissue Oxygenation and Altered Valsalva Hemodynamics in Young Adults with Type 1 Diabetes - Bitsch Poulsen, Maria; Oketa-Onyut Julu, Peter; Schah, Memon; Shah, Mussadiq; Brock, Christina (International Physiology Journal, 2026)
Aims Cardiac autonomic neuropathy is currently an untreatable progressive complication of type 1 diabetes (T1D). Impaired microcirculation is a suspected cause of nerve degeneration in TID. We investigated whether cardiovascular autonomic reflexes often used as indices of nerve functions, are associated with indices of microcirculatory function in young adults with T1D compared with non-diabetic controls. Methods In a cross-sectional study, 15 adults with T1D and 15 age-matched controls (20-40 years) underwent standardized cardiovascular autonomic reflex tests. Continuous recordings of electrocardiogram, cardiac vagal tone, beat-to-beat blood pressure and transcutaneous tissue oxygen (tcpO₂) and carbon dioxide partial pressures (tcpCO2) were done. Results Despite preserved baroreflex, parasympathetic, and sympathetic functions assessed using cardiovascular reflex tests, the individuals with T1D exhibited reduced baseline tcpO2 compared to the controls (37.5±3.75 vs. 49.6 mmHg). During the Valsalva manoeuvre, individuals with T1D exhibited a reduced systolic blood pressure response in phase I (31±10 vs. 43±18 mmHg) and early phase II (-1±15 vs. -18±17 mmHg), and an increased systolic (31±15 vs. 18±14 mmHg) and diastolic (45±11 vs. 33±16 mmHg) response in late phase II compared to controls. The early phase II diastolic response was inversely associated with baseline tcpO2. Conclusion The altered hemodynamic response to the Valsalva manoeuvre is suggestive of possible reduced arterial elasticity, higher vascular resistance, and splanchnic sympatho-vagal imbalance in T1D despite normal autonomic reflex ratios. The concomitant evidence of reduced tissue oxygenation and altered hemodynamics may represent early signs of dysautonomia but require longitudinal validation.
Keywords: type 1 diabetes; autonomic neuropathy; cardiovascular autonomic reflexes; cardiac vagal tone; tissue oxygenation